Utilização de bioinsumos em sementes de feijão e efeitos nos parâmetros agronômicos, fisiológicos e tecnológicos - Weber, Thaís (2023)
Beans are one of the main daily staple in the Brazilian diet and are considered a good source of protein, carrying essential nutrients. In addition to its importance in food, beans are widely produced throughout the country and their demand favors the price, especially for small producers. Due to these factors, studies that seek to improve the production of this species are of particular interest to the market, whether by increasing productivity, or even by using cleaner technologies, which are highly considered nowadays. Among these new technologies, the use of microorganisms, such as inoculation with Rhizobium tropici, which can replace the utilization of chemical nitrogen fertilizers, is a good option for use on bean crops. In addition, in recent years research into the use of yeasts in agriculture has grown, as they are capable of inducing resistance against diseases as well as produce plant hormones, favorable to plant development. One of these yeasts is Sporidiobolus johnsonii, which has potential application in improving seed quality. Therefore, the objective of this research was to evaluate the inoculation of bean seeds with Rhizobium tropici and filtrate of the yeast Sporidiobolus johnsonii, on the agronomic parameters of the crop and post-harvest quality of the grains. The experiment was set up according to a Randomized Complete Block Design (DBC) and the bean seed employed was IAC Veloz. The treatments were: T1 – Control (no treatment); T2 – Seed treatment with a synthetic commercial product based on nitrogen, potassium, organic carbon, and zinc; T3 – Seed treatment with Sporidiobolus johnsonii yeast filtrate; T4 – Inoculation with Rhizobium tropici; and T5 – Seed treatment with Sporidiobolus johnsonii filtrate product combined with Rhizobium tropici inoculation; in which each treatment has four replications, adding up to 20 experimental plots. The agronomic parameters of the bean plant were evaluated regarding productivity, number of pods per plant, number of grains per pod, weight of a thousand seeds, and nitrogen content of the leaves; the physiological quality of the bean as a seed, via germination test, vigor test, and emergence speed; in addition to determining the post-harvest quality of bean grains by cooking time. The yeast Sporidiobolus johnsonii is capable of producing gibberellin of the GA4 type, the most bioactive among all gibberellins and difficult to produce synthetically. The use of Sporidiobolus johnsonii yeast filtrate, co-inoculation with Rhizobium tropici and the combination of these treatments were not able to improve the agronomic and technological parameters of the bean plant.